Advances in Classical and Applied Mathematics (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
Progress within mathematics is based on innovative ideas comprising a kind of cycle that starts from an identified need to develop a solution. First of all, this need is transformed in a problem that must be clearly defined in order to find a solution.In classical mathematics, a lot of computations are involved, and domains are used (including in algebra, geometry, classical logic, set theory, mathematical analyses, statistics, etc.). Applied mathematics focuses on mathematical principles and involves the application of mathematics to problems that arise in various areas, such as engineering or other domains of science or life. All these inform the development of new or improved methods, which allow us to obtain solutions for new problems.